Determinação das estruturas cristalinas e moleculares de quatro derivados fenazínicos utilizando a difração de raios X - Soares, Janaína Gomes (2006)
This work aims the structural determination of phenazines compounds, and derivatives that present bioactivity for the treatment of malaria, using the X-ray diffraction method. Chapter 1 shows an introduction to pharmacologicol products and the importance of this structural resolution. Chapter 2 prejent the general characteristics of malaria in Brazil. Chapter 3 theoretical fundaments on the of X-ray diffraction technique, followed in chapter 4, by a description of the methods of crystallization and the steps of structural resolution. Finally, chapter 5, brings the discussion and results obtained in the structural resolution of four studed compounds. The studied phenazines composites were: 5,5-Dimetil-5,6-dihydro-7H- 4b,13-diazadibenzo[a,de]antracen-8-ona (FENA), 4-(3'-metil-but-2'-enil)-benzo[a]- fenazin-3-ona (FLA), cloro(dibenzo[a, c]fenazin-1-il-K2,C1, N14) piridinopaládio(II) (FENA-Pd), 8-bromine-7,7-dimethyl-5,10-dioxo-7,8,9,10- tetrahydro-5H-benzo[3,4 ] oxecino[5,6-b]quinoxaline-16-N-oxidates (FENA-Br). All the data collection had been obtained in on automatic KappaCCD diffractometer using MoKα monocromatic radiation, of wave length of 0.71073 Å (molybdenum). The compound called FENA crystallize in the monoclinic system and belongs to space group P21/a, with net parameters a = 7.1442(2) Å, b = 12.5463(3) Å, c = 17.1835(4) Å, β = 95.520(1) Å, with a volume, V = 1533.07(7) Å3. The calculation of the density, assuming Z = 4 molecules for unit cell, resulted in a value of 1.242 g.cm -3. The compound called FLA, crystallize in the monoclinic system and belongs to the space group C 2/c, with cell parameters of a = 21.0180(1)Å, b = 9.1359(3) Å, c = 17.7772(9) Å, β = 109.402(2), with a volume, V = 3219.70(24) Å 3. The calculation of the density, assuming Z = 8 molecules for unit cell, resulted in a value of 1.297 g.cm -3. The compound called FENA-Pd crystallize in the Monoclinic system, belongs to the space group P21/a, with parameters of a = 12.0413(4), b = 13.4986(6), c = 12.3869(5) Å, β = 106.074(2), V = 1934.6(1) Å3. The calculation of the density, assuming Z = 4 molecules for unit cell, resulted in a value of 1.72/g.cm-3 for the density of the crystal. The compound called FENA-Br, crystallize in the orthorombic system and belongs to the space group P 21 21 21, with cell parameters of a = 6.2552(1) Å, b = 14.6703(3) Å, c = 20.5061(5) Å, calculated density 1.558 g.cm -3, assuming Z = 4.